Differential response of the liver to bile acid treatment in a mouse model of Niemann-Pick disease type C - Nicoli, E; Smith, D; Morris, L; Platt, F (F1000Research, 2017)
Niemann-Pick disease type C (NPC) disease is a neurodegenerative lysosomal storage disease caused by mutations in the NPC1 or NPC2 genes. Liver disease is also a common feature of NPC that can present as cholestatic jaundice in the neonatal period. Liver enzymes can remain elevated above the normal range in some patients as they age. We recently reported suppression of the P450 detoxification system in a mouse model of NPC disease and in post-mortem liver from NPC patients. As bile acids regulate the P450 system, we tested bile acid treatment using ursodeoxycholic acid (UDCA; 3α, 7β-dihydroxy-5β-cholanic acid), a hydrophilic bile acid, which is used to treat several cholestatic disorders. In this study, we compared UDCA treatment with the bile acid cholic acid (CA), and found unexpected hepatotoxicity in response to CA in Npc1 mice, but not to UDCA, suggesting that only UDCA should be used as an adjunctive therapy in NPC patients.